Pinkalicious and the babysitter - Kann, Victoria (New York, NY : Harper, an imprint of Harper Collins Publishers, 2017)
When Peter breaks his mother's mug while Maya is babysitting him and Pinkalicious, Pinkalicious tries to turn the broken pieces into art.
Ages 4-8.
Keywords: Babysitters -- Juvenile fiction; Creative ability -- Juvenile fiction; Creative ability -- Fiction